John Singer Sargent and his muse : painting love and loss - Corsano, Karen; Williman, Daniel (Rowman and Littlefield, 2014)
This sensitive and compelling biography sheds new light on John Singer Sargent's art through an intimate history of his family. Karen Corsano and Daniel Williman focus especially on his niece and muse, Rose-Marie Ormond, who married the only son of André Michel, the foremost art historian of his day. Robert was a promising historian as well, until the Great War claimed him in 1914. His widow Rose-Marie served as a nurse for blinded French soldiers until she too was killed in 1918. Sargent expressed his grief on canvas, painting ruined French churches and, in Gassed, blinded soldiers; he made h.